Effect of light intencity on forages and seed production of Kalopo (Calopogonium muconoides) - Achmad Fanindi; B.R Prawiradiputra; L Abdullah (Jurnal Ilmu Ternak dan Veteriner, 2010)
Kalopo (Calopogonium mucunoides) was used as cover crops in plantation. Besides, kalopo can be used as forage, esspecially in dry season. The aim of this study was to evaluate the effect of light intensity on forage and seed production. Research was conducted at Research Institute for Animal Production, Ciawi Bogor and Laboratory of Agrostology Faculty of Animal Husbandry, Bogor Agricultural University, for 16 months. Four levels of light intensity, namely: 100%, 80%,60% and 40% were applied, leguminous species of kalopo (Calopogonium mucunoides), was used. Block Randomized Design with 3 replications was applied in this research. Data collected was analyzed by ANOVA and Duncan’s Multiple Range Test. Forage production was evaluated within one year. The forage quality and digestibility (invitro) were investigated. Seed production was accumulated as seasonal seed production during one year. The results showed that light intensity affected (P < 0.05) forage and seed production, chlorophyll and total chlorophyll of kalopo, but did not affect (P > 0.05) quality and digestibility of kalopo. Seed production of kalopo was affected (P < 0.05) by light intensity, the highest forage and seed production of kalopo were obtained from treatment of full light intensity (100%). The seed quality of kalopo was affected by light intensity. The best seed quality of kalopo was achieved from 80% light intensity. The result shows that plots with light intensity of 100% was the best light intensity for forage and seed production of kalopo. Kalopo could grow well in the plots up to 80% light intensity. Key Words: Light Intensity, Forage, Seed, Kalopo